MENTAL ILLNESS OF BRUCE WAYNE IN BATMAN BEGINS (2005) AND TONY STARK IN IRON MAN (2010) - Miranda, Lirang Titania; Sape'i, Sape'i; Assiddiqi, Hasbi (Universitas Islam Negeri Sunan Gunung Djati, 2023)
Literary psychology is defined as a field of study that examines literary works that involve fictional or factual characters acting out events from human life. Superheroes figure started to show up in 1930s, their characters were always written as a perfect human being due to the WW II. This study compared mental illnesses encountered by the two major protagonists in Christopher Nolan's Batman Begins (2005) and Jon Favreau's Iron Man 2 (2010) films. Mental issues have been very openly discussed in the current days and there are lots of movies which started to portray mental issues in the story, including superhero movies. This was a comparative literature from Bassnett (1993) and Damono (2009) to discover the similarities and differences between the characters, as well as Psychology of Literature by Minderop (2010) assisted by structuralism theory and theories of mental disorder from psychology. This study used a qualitative method. The results showed that Batman and Iron Man suffer from several mental illnesses, such as: depression, anxiety, antisocial, schizoid, PTSD, narcissistic, histrionic, and OCD. The study concluded that both main characters as the centre of the story who have an internal problem within themselves because of their mental illnesses.Â Keywords: comparative literature, psychology of literature, mental illness, main character